Etiology and treatment of dentin hyperesensitivity today: integrative review (Research, Society and Development, 2020)
Objective: To analyze the literature about the etiological factors related to dentin hypersensitivity. Methodology: This is na integrative literature review using scientific articles from the SciELO, Lilacs and BBO research bases. The search was basad on articles between the years 2010 to May 2020 and among the selected ones, the objective was to clarify “What are the origins and possible treatments for dentin hypersensitivity?”. For the selection of these articles, the following descriptors were used: “Pain”, “Dentistry” and “Dentin Sensitivity”. These were individually researched and, afterwards, a search was made with crossings between them, using the "AND". Results: After analyzing the scientific articles that were included in this review, it was found that, based on the inclusion criteria previously established, a final sample with nine scientific productions was identified, with a variety of treatments that aim to eliminate or reduce factors impaired by dentinal sensitivity. Conclusion: It is concluded that there are several factors related to dentin hypersensitivity and also the treatment options, requiring a thorough diagnosis to plan and provide the best therapy option for the patient.